Effectiveness of Lontar Sap Vinegar and Lime Juice as a Substitute for HCl in the Production of Skipjack Fish Bone Gelatin - Naema Bora; Anastasia Grandivoriana Nomi (The University of Lampung, 2025)
Gelatin is a product of collagen hydrolysis that is widely used in the food, pharmaceutical, and cosmetic industries. The gelatin production process generally uses hydrochloric acid (HCl) as a hydrolysis agent, but its use raises concerns about the environment and food safety. This study aims to evaluate the effectiveness of palm sap vinegar and lime juice extract as a substitute for HCl in the production of gelatin from skipjack fish bones (Katsuwonus pelamis). The study used a 3 x 3 factorial design with two main factors, namely the type of acid compound (HCl, coconut sap vinegar, and lime juice extract) and the acid concentration (5%, 7%, and 9%). The variables observed included yield, pH, moisture content, ash content, fat content, and gelatin protein content. The results showed that the type of acid and the con-centration of acid significantly affected the quality of gelatin. Palm sap vinegar produces gelatin with characteristics almost equivalent to HCl, with the highest protein content of 53.77%. Meanwhile, lime juice extract produced lower protein content (48.87%) yet provided lower fat content. The 7% and 9% acid concentration produces gelatin of the highest quality in terms of yield and protein content. This study shows that palm sap vinegar can be environmentally friendly and effective alternatives to replace HCl in gelatin production, with some adjustments to their concentration and application. Keywords: Acid concentration, Gelatin skipjack fish bones, Lime juice extract, Palm sap vinegar.